Neurocognitive dysfunction in adolescents with recent onset major depressive disorder: a cross-sectional comparative study - Bienek, Olga; Allott, Kelly; Antonucci, Linda; Bertolino, Alessandro; Bonivento, Carolina; Borgwardt, Stephan; Brambilla, Paolo; Chisholm, Katharine; Dannlowski, Udo; Lichtenstein, Theresa K.; Kambeitz, Joseph; Kambeitz-Ilankovic, Lana; et al. (SPRINGER, 2025)
The aim of this study was to examine the neurocognitive deficits associated with the first episode of major depressive disorder (recent onset depression, ROD) in adolescents as compared to adult patients. Cross-sectional neurocognitive data from the baseline assessments of the PRONIA study with N = 650 (55.31% females) were analyzed. Based on a principal component analysis of eleven neurocognitive tests, we constructed an overall neurocognitive performance (NP) score. We examined mean score differences in NP between the groups of healthy controls (HC) and ROD and between adolescents (15-21 years) and adults (22-40 years) within a GLM approach. This accounts for unbalanced data with focus on interaction effects while controlling for effects of medication and educational years. Our results show lower NP for the ROD as compared to the HC group (d = - 0.29, p = .046) and lower NP for the adolescent group as compared to the adult group (d = - 0.29; p < .039). There was no interaction between these two group effects (F = 1.11; p = .29). Our findings suggest that the detrimental effect of ROD on neurocognitive functioning is comparable in adolescent and adult patients, since lower scores in adolescent patients are explained by effects of age and education. Neurocognitive impairment is an under addressed issue in clinical treatment guidelines for adolescent MDD. We suggest efficient monitoring in clinical practice by using an aggregate of the Digit Symbol Substitution Test and the Trail Making Test B, which highly correlated with the overall score of NP (r = 0.82).